Hotel las Islas: Guest satisfaction with a tourist product service (2022)
Providing excellent quality standards has become one of the factors that determine the success of companies providing accommodation services (Falces et al., 1999). Experiences in hospitality and tourism services are the main product of the sector with impact and influence on its competitiveness. Satisfying guests is the ultimate goal of every hotel business, In this context it has a relevant role in the commercial domain and is a starting point on the economy of experience in the sector. The aim of this work is to contribute to the understanding of how the innovation of new tourism products/services could potentially enhance tourism experience by offering more personalized alternatives to meet the unique needs and preferences of each visitor. Grönroos (1984) points out that the quality of services must be seen from the perspective of the customers, stating that "it is the result of an evaluation process, where the consumer compares his expectations with the perception of the service he has received".